SIKAP REMAJA TERHADAP MASALAH GIZI PADA REMAJA DI PANTI ASUHAN - Pujiati Setyaningsih; Jumiatun Jumiatun (Siklus : Journal Research Midwifery Politeknik Tegal, 2022)
Adolescence is a period of transition and change, a period of trouble and the search for identity. One of the health problems is related to adolescent nutrition. Riskesdas 2018 data shows that 25.7% of people aged 13-15 years and 26.9% of people aged 16-18 years have short and very short nutritional status. 8.7% of people aged 13-15 years and 8.1% of people aged 16-18 years are thin and skinny. Overweight and obesity is 16.0% in people aged 13-15 years and 13.5% in people aged 16-18 years. Based on the 2017 UNICEF baseline survey, it was found that there were changes in diet and physical activity in teenagers. Teenagers use their free time for passive activities, and consume unhealthy foods and drinks. This study was conducted to determine the attitude of teenagers towards nutritional problems, with the respondents being teenagers themselves. The results are most of the respondents had a good attitude towards nutritional problems, but there were still a small number who were less concerned about their nutritional problems. Therefore, there will be efforts to motivate adolescents to behave through programmed communication, education related to health and nutritional problems, considering the importance of nutrition for growth and development of adolescence.